Pengaruh Lingkungan Kerja Fisik dan Loyalitas Kerja terhadap Kinerja Pegawai pada Kecamatan Cibungbulang di Kabupaten Bogor - Ariyanti, Eti; Wardani, Endang Susilo; Irawati, Laila (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
Employee performance is one of the most critical aspects that determine the quality of public services, especially at the sub-district government level. In this context, understanding the factors that influence performance, such as the physical work environment and work loyalty, becomes essential to improve service delivery and organizational effectiveness. This study aims to investigate the effect of the physical work environment and work loyalty on employee performance at the Cibungbulang Sub-District Office, Bogor Regency, both partially and simultaneously. This study employed a quantitative approach. The population consisted of 59 respondents, and a saturated sampling technique was used, meaning that the entire population was taken as the sample. As a result, the total sample size was 59 individuals. Data analysis was conducted through several stages, including validity testing, reliability testing, classical assumption testing, regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing. The findings reveal that the physical work environment has a strong and positive relationship with employee performance. A conducive physical environment not only enhances comfort and safety but also supports productivity and motivation, leading to improved individual performance. Similarly, work loyalty shows a very strong connection to performance. Loyal employees tend to have a deeper commitment to their duties, greater responsibility, and a stronger drive to contribute to the organization's goals, which significantly improves their work output. When both variables—physical work environment and work loyalty—are examined together, they show a significant simultaneous effect on employee performance. This suggests that efforts to enhance physical workplace conditions and foster employee loyalty should be prioritized together, as their combined influence can drive meaningful improvements in public service performance.